STRATEGI KOMUNIKASI EKSTERNAL DIREKTORAT RESERSE NARKOBA POLDA KEPRI DALAM PENYEBARAN NARKOBA DI KOTA BATAM - Framana, Qori; Cindoswari, Ageng Rara (LPPM Universitas Putera Batam, 2023)
Drugs pose a serious threat to society. Th e Directorate of Drug Investigation of the Riau Islands Regional Police plays a crucial role in efforts to prevent and combat drug trafficking in the region. This research aims to examine the communication strategies employed by the Directorate of Drug Investigation of the Riau Islands Regional Police in drug prevention and control. The study adopts qualitative research methods with a narrative study approach. Data is collected through in-depth interviews with officers and officials from the Directorate of Drug Investigation, as well as documentation related to the implemented communication strategies. The research also draws upon the system theory developed by Ludwig von Bertalanffy. The research findings indicate that the Directorate of Drug Investigation of the Riau Islands Regional Police has implemented various communication strategies in their efforts to prevent and combat drug trafficking. The study concludes that effective and sustainable communication strategies are key in the prevention and control of drug trafficking.